The Experience And Legal Foundations Of Compulsory Medical Insurance In The Russian Federation (The Journal of Interdisciplinary Human Studies, 2026)
This thesis examines the experience and legal foundations of compulsory medical insurance (obyazatelnoye meditsinskoye strakhovaniye, OMS) in the Russian Federation. Medical insurance is one of the most important financial mechanisms for the stable provision of health-care services to the population, and in the Russian Federation the OMS system is one of the principal sources of financing health care. On the basis of Federal Law No. 326-FZ of November 29, 2010, “On Compulsory Medical Insurance in the Russian Federation,” the thesis sets out the subject matter and legal basis of the system, its principal concepts, and the basic principles by which it is implemented.
Keywords: compulsory medical insurance; OMS; Russian Federation; health- care financing; legal foundations; Federal Law No. 326-FZ; insured person; insurance premium; basic program; territorial program